Fabrication and characterization of nano-TiO[2] thin films from local mineral precursors / Mahdi Ezwan Mahmoud - Mahdi Ezwan, Mahmoud (2012)
Ilmenite is a tin mining byproduct that contains the radioactive element Uranium (U) and Thorium (Th). Although present in minute amounts (300-400 ppm), Malaysian law (Act 304) stipulates that it is radioactive, and is therefore a schedule waste, and need to be dealt with accordingly. The disposal cost is too high, prompting the companies involved to reprocessed ilmenite into synthetic rutile via hydrometallurgy, a low grade TiO2 intermediate compound. Synthetic rutile contains mostly TiO2 in the rutile phase, iron, silicon and other impurities, making it highly impractical for any high-end usage. Due to this fact, its cost is quite low. TiO2 is a common compound that is most famous for use as white pigmentation in paints, due to its whitish colour. In the nanosize region, its applications are much more diverse, including self-cleaning coatings, electrochromism, and photocatalytic applications. It also comes in many forms such as tubes, particles, and spheres. TiO2’s flexibility allows it to be processed from many methods, such as solgel, hydrothermal, solvothermal and sonochemical method, with each method producing unique products that is suitable for differing applications. There are two objectives to this work, the first objective is utilize a tin mining byproduct (ilmenite) to produce anatase nano-TiO2 particles, and the second objective is to use these particles to produce nano-TiO2 thin films. The processing methods to produce both the particles and thin films will be modified from conventional methods in order to suit the nature of the intended precursors. We intend to use low grade synthetic rutile, derived from ilmenite, as a precursor to produce anatase nano-TiO2 particles. The method that is going to be utilized is the hydrothermal method, although, due to the nature of the precursor, the method needs to be modified. The product from this process will in turn be used as a precursor to produce nano-TiO2 thin film, utilizing the solgel method. This solgel method also needs to be slightly modified due to the presence of impurities in the sample. The properties that needs to be analyzed is the chemical composition of the samples, the crystallite size of the particles, its surface area, morphology for the nanoparticles, and the film thickness, transparency, morphology, topography, and phases for the thin film. To this end, characterization methods such as the XRD, SEM, BET, AFM, UV-Vis, and the surface profiler will be used. A control nanoparticle sample, purchased from American Elements, will be compared to our nanoparticles, for the thin films, data from literature will be used as comparison. The proposed methods manage to produce both the nanoparticles and thin films successfully. We also discovered that in some aspects, such the crystallite size and surface area, it is better than the commercial product. The thin film’s morphology and surface profile (rough), low thickness and relatively high transmission indicates its suitability for photocatalytic and self-cleaning applications. The films are also relatively pure, with TiO2 dominating the content of the films. The results indicate that it is possible to convert a low quality waste product into a high quality usable nanomaterial with a multitude of potential applications. The resulting product is in some ways superior to commercial products, and the processing method is cheap, environmentally friendly and easily customizable.